Recent trends in productivity in China shift-share analysis of labour productivity growth and the evolution of the productivity gap - Molnar, Margit (OECD Economics Department Working Papers, 2015)
The Chinese economy has been undergoing fundamental structural changes since the start of reforms in 1978. An increasing number of farmers first got engaged in off-farm activities and then started to migrate to cities in the 1990s in search of jobs. Such movement of labour from less to more productive jobs boosted overall labour productivity and growth. Agglomeration and scale economies further pushed up productivity. While the productivity gains from internal migration will diminish gradually over time, urbanisation is likely to remain an important source of productivity growth in the coming decade or so. This paper first decomposes labour productivity growth over 2000-11 into a within-industry, a shift and a cross effect in a number of countries and compares China with other countries over this period. This shift-share analysis also allows a comparison of within-sector productivity gains across a large number of sectors and countries. Labour productivity alongside total factor productivity is also discussed from the perspective of its gap with the United States and growth rate over 2000-11 and in comparison with other BRIICS economies. In this analysis, manufacturing and service industries are looked at separately. This Working Paper relates to the 2015 OECD Economic Survey of China www.oecd.org/eco/surveys/economic-survey-china.htm